Paulo Freire: historia y utopía (homenaje en el centenario de su nacimiento) (2022)
Presented are some ideas of Paulo Freire about history and specifically his criticism of postmodernism with his ideology of the end of history, the end of socialism, the end of utopia and the end of ideologies. Emphasis is placed on the critical and liberating position of Brazilian educators beliefs.